Precise engineering of hybrid molecules-loaded macromolecular nanoparticles shows in vitro and in vivo antitumor efficacy toward the treatment of nasopharyngeal cancer cells - Dongmei Liu; Wenguang Zhang; Xinju Liu; Rongliang Qiu (Drug Delivery, 2021)
Cancers continue to be the second leading cause of death worldwide. Despite the development and improvement of surgery, chemotherapy, and radiotherapy in cancer management, effective tumor ablation strategies are still in need due to high cancer patient mortality. Hence, we have established a new approach to achieve treatment-actuated modifications in a tumor microenvironment by using synergistic activity between two potential anticancer drugs. Dual drug delivery of gemcitabine (GEM) and cisplatin (PT) exhibits a great anticancer potential, as GEM enhances the effect of PT treatment of human cells by providing stability of the microenvironment. However, encapsulation of GEM and PT fanatical by methoxypoly(ethylene glycol)-block-poly(D, L-lactic acid) (PEG-PLA in termed as NPs) is incompetent owing to unsuitability between the binary Free GEM and PT core and the macromolecular system. Now, we display that PT can be prepared by hydrophobic coating of the dual drug centers with dioleoylphosphatidic acid (DOPA). The DOPA-covered PT can be co-encapsulated in PLGA NPs alongside GEM to stimulate excellent anticancer property. The occurrence of the PT suggestively enhanced the encapsulations of GEM into PLGA NPs (GEM-PT NPs). Further, the morphology of GEM NPs, PT NPs, and GEM-PT NPs and nanoparticle size was examined by transmission microscopy (TEM), respectively. Furthermore GEM-PT NPs induced significant apoptosis in human nasopharyngeal carcinoma CNE2 and SUNE1 cancer cells by in vitro. The morphological observation and apoptosis were confirmed by the various biochemical assays (AO-EB, nuclear staining, and annexin V-FITC). In a xenograft model of nasopharyngeal cancer, this nanotherapy shows a durable inhibition of tumor progression upon the administration of a tolerable dose. Our results suggest that a macromolecular hydrophobic and highly toxic drug can be rationally converted into a pharmacologically efficient and self-deliverable of nanotherapy.